Chinese version of the Physical Resilience Scale (PRS): reliability and validity test based on Rasch analysis - Aohua Dong; Huijun Zhang; Linghui Kong; Tingting Lu; Chen Zheng; Fangzhu Ai; Fuzhe Feng (BMC, 2024)
Abstract Background Physical resilience is known to minimize the adverse outcomes of health stressors for older people. However, validated instruments that assess physical resilience in older adults are rare. Therefore, the purpose of this study was to translate the Physical Resilience Scale (PRS) into Chinese and to validate its psychometric properties in a population of community-dwelling older adults following SARS-CoV-2 infection. Methods This study used a cross-sectional design and translated the Physical Resilience Scale into Chinese. A total of 426 older adults who had recovered from SARS-CoV-2 infection were chosen for assessment through convenience sampling. The measurement data were analyzed using the Rasch analysis. Results Rasch analysis indicates that the Physical Resilience Scale demonstrates excellent reliability, validity, and unidimensionality. The Infit MNSQ and Outfit MNSQ of each entry were 0.77 ~ 1.19, and the degree of fit of each entry to the scale was good. Person and item separation reliability support the internal consistency of the studied samples and PRS items. Conclusions The Physical Resilience Scale has good reliability and is suitable for the assessment of physical resilience tests in older people. However, the overall difficulty of the scale is not suitable for older adults of all ability ranges, and it is possible to add higher and lower difficulty items and adjust the difficulty spacing between items in a later study.